SULFATED FUCOIDAN HYDROGEL FROM Undaria pinnatifida AS A HIGH-PERFORMANCE BIOADSORBENT FOR CADMIUM REMOVAL FROM WASTEWATER (Journal of Medical & Health Sciences Review, 2025)
Cadmium (Cd²⁺) must be effectively removed from effluent because of its high toxicity and persistence in aquatic settings. In this work, Undaria pinnatifida was used to create a sulfated fucoidan hydrogel (FUC-HG), which was then tested as a high- performance bioadsorbent for Cd2+ sequestration. A maximal adsorption capacity of approximately 50 mg g⁻¹ was made possible by the hydrogel's heterogeneous surface with numerous active binding sites. While kinetic analysis followed the pseudo-second- order model (R²=0.9876), confirming chemisorption as the main mechanism, equilibrium data fitted the Freundlich isotherm (R²=0.9441), showing multilayer adsorption. According to thermodynamic investigations, the reaction was spontaneous, endothermic, and entropy-driven, which is in line with chemical interactions between the hydroxyl and sulfated functional groups of FUC-HG and Cd²⁺ ions. Elovich and intraparticle diffusioninvestigations, which emphasised surface binding followed by pore diffusion, provided additional evidence for sequential uptake.Over several cycles, the hydrogel showed outstanding durability and reusability while retaining a high adsorption efficiency. These findings establish FUC-HG as an economical, selective, and eco- friendly bioadsorbent with great promise for real-world use in industrial heavy metal remediation and wastewater treatment.